4
$\begingroup$

Given that $$a+b+c=2$$ and $$ab+bc+ca=1$$ Then the value of

$$(a+b)^2+(b+c)^2+(c+a)^2$$ is how much?


Attempt:

Tried expanding the expression. Thought the expanded version would contain a term from the expression of $a^3+b^3+c^3-3abc$, but its not the case.

$\endgroup$
  • $\begingroup$ $$(a+b)^2+(b+c)^2+(c+a)^2 = 4 + a^2 +b^2+c^2 = \ldots$$ $\endgroup$ – Kevin Jul 4 '17 at 13:29
  • $\begingroup$ Why would you think of $a^3+b^3+c^3-3abc$, when $(a+b+c)^2$ will lead you to the solution? $\endgroup$ – MAN-MADE Jul 4 '17 at 13:42
  • $\begingroup$ The accepted answer claims we know $a^2 + b^2 + c^2$, but this is not given. Do you have a typo'? $\endgroup$ – Eric Towers Jul 4 '17 at 19:51
  • $\begingroup$ @DaanvdWoude : You're out of sync. lioness99a has corrected her answer to derive this result. $\endgroup$ – Eric Towers Jul 7 '17 at 4:01
7
$\begingroup$

We can expand $$(a+b)^2+(b+c)^2+(c+a)^2$$ to get

$$2 a^2 + 2 a b + 2 a c + 2 b^2 + 2 b c + 2 c^2 $$

We can rearrange this to be more useful:

\begin{align}2 a^2 + 2 a b + 2 a c + 2 b^2 + 2 b c + 2 c^2 &= 2 a^2 + 2b^2+2c^2 + 2 a b + 2 a c + 2 b c\\ &=2(a^2+b^2+c^2)+2(ab+ac+bc)\end{align}

We know the value of $ab+ac+bc$, so we can say that \begin{align}2(a^2+b^2+c^2)+2(ab+ac+bc)&=2(a^2+b^2+c^2)+2\end{align}

Now we need to find the value of $a^2+b^2+c^2$.

We can do this as follows:

\begin{align}(a+b+c)^2&=2^2\\ a^2 + 2 a b + 2 a c + b^2 + 2 b c + c^2&=4\\ a^2+b^2+c^2+2(ab+ac+bc)&=4\\ a^2+b^2+c^2+2\times 1&=4\\ a^2+b^2+c^2&=2\end{align}

So now we can say that \begin{align}2(a^2+b^2+c^2)+2&=2\times 2+2\\ &=6\end{align}

$\endgroup$
  • $\begingroup$ You claim "we know the values of $a^2 + b^2 + c^2$ ...", but this value is not given. Have you skipped a step? $\endgroup$ – Eric Towers Jul 4 '17 at 19:52
  • $\begingroup$ @EricTowers Ooops, misread the first line of the question as $a^2+b^2+c^2=1$..! Have edited my answer and corrected for that now $\endgroup$ – lioness99a Jul 4 '17 at 19:58
5
$\begingroup$

If you just want the value of expression $(a+b)^2 + (b+c)^2 + (a+c)^2$than set the vale of $a=0$, $b=1$ and $c=1$ (these satisfy the required conditions ) and you are going to get the answer.

$$(1)^2 + (2)^2 + (1)^2 = 6$$

$\endgroup$
  • 2
    $\begingroup$ This somehow feels very wrong. $\endgroup$ – A---B Jul 4 '17 at 13:44
  • $\begingroup$ @ A---B Please tell me where I am is wrong $\endgroup$ – user275490 Jul 4 '17 at 13:46
  • 1
    $\begingroup$ I agree with @A---B. Think it is worth adding a bit of clarification about why you are able to do this. We're not saying you are wrong, just that it feels like a very uniniuitive way of doing it $\endgroup$ – lioness99a Jul 4 '17 at 13:46
  • 6
    $\begingroup$ @A---B: It feels wrong because it presumes (as does the original question, depending how one parses!) that the value of $(a+b)^{2} + (b+c)^{2} + (a+c)^{2}$ depends only on the values of $a + b + c$ and $ab + bc + ca$. If one grants the fact, Get-u's approach is about as elegant as one can want. (The other solutions establish this fact by algebra, of course.) $\endgroup$ – Andrew D. Hwang Jul 4 '17 at 15:23
3
$\begingroup$

Hint:

Express $S_2=a^2+b^2+c^2$ in function of $s=a+b+c$ and $\sigma=ab+bc+ca$ from the algebraic identity for $(a+b+c)^2$.

$\endgroup$
3
$\begingroup$

Either you are using a clever identity (see the other answers), or you just substitute $c=2-a-b$ so that
$$ ab+bc+ca-1=- a^2 - ab + 2a - b^2 + 2b - 1, $$ and compare it to the identity in question $$ (a+b)^2+(b+c)^2+(c+a)^2=2a^2 + 2ab - 4a + 2b^2 - 4b + 8. $$ This may not be elegant, but at least you know how to do it yourself.

$\endgroup$
  • $\begingroup$ $(a+b+c)^2=a^2 + b^2 + c^2 +2ab+2bc+2ac$ is not a very clever identity. $\endgroup$ – A---B Jul 4 '17 at 13:33
  • $\begingroup$ @A---B But it is clever to consider the identity here. As a beginner you may not see this immediately. $\endgroup$ – Dietrich Burde Jul 4 '17 at 13:39
3
$\begingroup$

If you expand you find its $a^2+b^2+c^2+2ab+2bc+2xa+a^2+b^2+c^2$. Now square first equation and we have $a^2+b^2+c^2+2ab+2bc+2ac=4. ..(3)$ thus now we want value of $4+a^2+b^2+c^2$ .rearranging $3$ and using your equation $2$ we have $a^2+b^2+c^2+2 (ab+bc+ac)=4$ thus $a^2+b^2+c^2+2=4$ thus value of expression we want is $4+a^2+b^2+c^2=4+2=6$

$\endgroup$
2
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\i}{\mathrm{i}} \newcommand{\text}[1]{\mathrm{#1}} \newcommand{\root}[2][]{^{#2}\sqrt[#1]} \newcommand{\derivative}[3]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\abs}[1]{\left\vert\,{#1}\,\right\vert}\newcommand{\x}[0]{\times}\newcommand{\summ}[3]{\sum^{#2}_{#1}#3}\newcommand{\s}[0]{\space}$

$=\boxed{2a^2 + 2b^2 +2c^2 + 2ab + 2bc + 2ac}$

$2(ab + bc +ac) = 2$

$\boxed{2a^2 + 2b^2 +2c^2 + 2}$

$a^2 + b^2 + c^2 = (a+b+c)^2 -2ab - 2bc -2ac$

$a^2 + b^2 + c^2 = (2)^2 -2$

$a^2 + b^2 + c^2 = 2$

$\bbx{\color{red} {2\times 2 + 2 =6}}$

$\endgroup$
1
$\begingroup$

$(a+b)^2 + (b+c)^2 + (a+c)^2=a^2+b^2+c^2+2ab+2bc+2ac=2(a^2+b^2+c^2)+2(ab+bc+ac)=2(a^2+b^2+c^2)+2 \cdot 1=2((a+b+c)^2-2(ab+bc+ac))=2 \cdot (2)+2=6$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.